A CBI Module and User Guide for Teaching Organic Chemistry - Painter, Frances (My University, 2000)
This project presents the development of a lesson design format on "Introduction to Organic Chemistry" for CBI - computer-based instruction. The design is to be used with the authoring program, Private School, an intelligent delivery system database.
The community college system has experienced many changes over the past few years. The changing political, economic and social climate has forced the community college system to re-examine how courses are delivered. Along with this, employers are demanding computer-literate students. There is a need for teachers to look at alternative delivery methods such as CBI. The addition of Computer-based learning to the chemistry curriculum at the community college is designed to do just that. CBI enhances student learning by providing an alternative delivery methodology for studying chemistry concepts, which can be abstract and difficult to comprehend.
Computer-based learning has been slow to be implemented at community colleges. This lesson, designed for the computer courseware database, Private School, offers community college teachers a framework to use for their own curriculum initiatives, thus allaying some of the fears and anxieties associated with computer technology.
Throughout the development of the computer-based instructional package, teacher involvement is critical. The success of such a teaching medium depends upon the commitment of the teacher/designer. The monitoring of student learning and of student progress must be built into the design.
The instructional development model of Kemp, Morrison and Ross was used as the foundation for making decisions about instructional objectives, content, learning activities, resources, learner characteristics and student evaluation. The curriculum was then used as an example for the User Guide to help teachers with the development of their own CBI. This project describes 5 phases for the implementation of CBI into community colleges: teacher familiarization, instructional design, data entry, student familiarization and student evaluation and progress.
CBI can provide resources for learning which are effective, richer, available for longer hours, and open to a wider range of college students. CBI also provides students with greater control over timing and pace, and there is more likelihood of resources suiting their style and stage of each student's learning.
Keywords: module, teaching, organic, chemistry, students, CBI, technology, curriculum